Transfer Pricing Documentation in a Post-BEPS environment : a study of the evolution of transfer pricing documentation in South Africa and its alignment with the global standard - Sukhlal, Limahl (My University, 2019)
n terms of the South African Income Tax Act 58 of 1962 (“the Act”), the South African Revenue Service (“SARS”) has the power to make transfer pricing adjustments. This arises when SARS deems that Multinational Entities (“MNE”) have been transacting at prices which do not reflect prices expected to be charged if parties to the transaction were independent persons dealing at arm’s-length. By having the ability to make transfer pricing adjustments, SARS can minimise the effects of Base Erosion and Profit Shifting (“BEPS”).1 BEPS refers to tax planning strategies that shift profits from high tax jurisdictions like South Africa to locations where little or no corporate tax is being paid. In order to provide governments with the necessary domestic and international instruments to prevent companies from paying limited amounts of taxes, the Organisation for Economic Co-operation and Development (“OECD”) formulated the BEPS Action Plan at the request of the G20. The BEPS Action Plan consists of 15 Action Points with the objective of minimising or eliminating transactions that erode or decrease a MNE’s tax base by routing its profits from high tax jurisdictions to low tax jurisdictions. The overriding concept of the BEPS Action Plan is that all taxable profits should be taxed once. Among the 15 Action Points addressed in the BEPS Action Plan, Action 13 which provides guidance on transfer pricing documentation and Country-by-Country reporting (“CbCR”), provides one of the bigger challenges to taxpayers in terms of transparency and disclosure This approach to transfer pricing documentation provides tax authorities with relevant and accurate information to perform an effective transfer pricing risk analysis.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Commerce (Specialising in Taxation)
Keywords: Transfer pricing; International economic relations; Transfer pricing--Taxation